Carbon monoxide oxidation using cobalt catalysts: a short review - Rattan, Gaurav; Kumar, Maninder (Publishing House of Lviv Polytechnic National University, 2014)
The preparation methods and main characteristics of known catalysts for carbon monoxide oxidation have been examined. A short review in a tabular form which facilitates a quick view on catalysts for CO oxidation (mainly cobalt ones) is represented. Розглянуто методи приготування і основні характеристики відомих каталізаторів для окиснення монoксиду вуглецю. В табличній формі приведено короткий огляд літератури основних металовмісних каталізаторів (головним чином, кобальтових) для реакцій окиснення СО.
Окиснення моноксиду вуглецю з використанням кобальтових каталізаторів: короткий огляд
Keywords: cobalt; catalyst; carbon monoxide; oxidation; catalytic convertor; automobile exhausts; кобальт; каталізатор; моноксид вуглецю; каталітичний конвертор; автомобільні вихлопи